Solving B- spline functions - Baghdad Science Journal (مجلة بغداد للعلوم, 2006)
In this paper, we proposed to zoom Volterra equations system Altfazlah linear complementarity of the first type in this approximation were first forming functions notch Baschtdam matrix and then we discussed the approach and stability, to notch functions